Building Communication and Capacity Among Guidance Advocates in Advocating Students’ Mental Health - Abegail Panghulan (Journal of Healthcare and Biomedical Science, 2025)
The main thrust of this study was to explore the challenges encountered by guidance advocates in addressing students’ mental health in the Division of Calamba City. Qualitative research, specifically the phenomenological approach, was utilized. The data was gathered through interviews with the eight (8) guidance advocates. Based on the guidance advocates' experiences, ten (10) themes emerged from the phenomenological study of guidance advocates. These are: Degrees of Familiarity, Developed Professional Skills, Obligation Focused, Diverse Guidance Advocates Roles, Guide, Immediate Response to Students’ Needs, Visible Changes in Students’ Behavior and Difficulty in Assessing, Communication and Capacity, Divine Intervention and Personal Motivation, Through Seminars and Trainings. Guidance advocates were able to describe a variety of challenges in supporting the mental health of the students, including: Reaching out, Lack of Professional Capacity, Encourage Students to Open up, Students with Separation Anxiety, Handling a Situation, and Emotional and Physical Preparedness. Rooted in the lived experiences of the guidance advocates, communication barriers and a lack of professional capacity to effectively advocate for students' mental health were the two main issues faced by the guidance advocates in the field. Each advocacy role faced unique obstacles, often compounded by a lack of training and institutional support. Despite these obstacles, self-motivation and faith-based coping mechanisms were frequently used by guidance advocates to manage their duties and carry-on providing students with effective support. Considering the results, the study suggests an improvement project called Project I.S.I.P. (Initiated Strategies Inspired by Professionals), a referral and counseling program intended to strengthen school-based mental health support networks and advocacy.